Identification of lumbar intervertebral space: palpation versus ultrasound technique among obese subjects - Selvakumar A,; Lee, Choon Yee (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Accurate identification of the intervertebral space (IVS) is necessary during central neuraxial blockade, especially in spinal anaesthesia, to avoid untoward spinal cord injury. Ultrasound guided examination has been shown to be more accurate compared to palpation, but these studies were performed on subjects of various body weights. We conducted our prospective observational study on obese subjects and compared the performance by anaesthesiologists of various levels of anaesthetic experience. Obese subjects with body mass index (BMI) ≥ 30 kg/m2 scheduled for elective surgery were recruited following explanation and written consent. With the subjects in the sitting position, an investigator located the L3-L4 IVS by ultrasound and used an invisible ultraviolet marker pen to mark the upper border, lower border and midpoint (“Point M”) of the space. Two anaesthesiologists of varying levels of experience, categorized as Performer 1 and Performer 2, then located the L3-L4 IVS by palpation. The distance between this point and Point M was measured and recorded. Thirty-two subjects with mean BMI 35.4±6.0 kg/m2 were recruited. The mean intervertebral distance at L3-L4 on ultrasound was 1.5 cm [range 1.2-1.8 cm]. By palpation, the L3-L4 IVS was correctly identified by 56.3%, while a higher IVS was mistaken to be L3-L4 by 23.4% of all performers. The space was correctly identified by 50% of junior anaesthesiologists and 62.5% of the senior counterparts. There was fair agreement between the two categories, with kappa = 0.375 and p = 0.028. In conclusion, there was a sizeable discrepancy between the anaesthesiologists’ estimation by palpation and the actual location of the L3-L4 IVS by ultrasound among obese subjects. This observation was in fair agreement among anaesthesiologists of various levels of anaesthetic experience. The ultrasound-guided technique is useful for better identification of lumbar IVS especially in obese subjects.